PENGUATAN AKAD PEMBIAYAAN MUDHARABAH UNTUK MEREALISASIKAN MISI KEADILAN BERBISNIS PADA BAITUT TAMWIL TAMZIS WONOSOBO - Fatoni, Nur (Economica: Jurnal Ekonomi Islam, 2012)
Baitut Tamwil TAMZIS is unique in terms of financing agreement courage to apply to the majority of its financing. BT TAMZIS understand the financing as "nggaduhke" of funds to members to be developed by way of trade. The risk of losses on these funds BT TAMZIS risk. This is evident when there is a fire Wonosobo market, Waterford and Magelang. To overcome it, he has a security system when there is a loss of assets due to natural factors or human error accident outside as the fire. He made the assurance division that serves as an internal insurance. Guarantee fund paid for by the BT TAMZIS in a unique way as well. Members exempt from administrative costs at the time of withdrawal. Members receive financing without the discount. He was obliged to pay the funds taawun with specific tariff. The benefit fund is to liberate the remaining debt taawun members during a disaster.